The Role Of Periapical Radiography As A Clinical Guide In The Bypass Procedure Of A Fractured Endodontic File In The Root Canal Of Tooth 22: A Case Report - Agung Nugroho; Nilasary Rochmanita Suparno; Cahyani Cahyani; Aulia Salsabila Agata (CV. AFDIFAL MAJU BERKAH, 2026)
Instrument fracture is one of the most common procedural complications encountered in endodontic treatment, with an incidence ranging from 0.25% to 10%. A fractured file retained within the root canal may hinder adequate debridement and obturation, thereby significantly affecting the prognosis of treatment. Periapical radiography plays a crucial role as both a diagnostic modality and a clinical guide in the management of such cases. This case report describes the management of a fractured instrument in the root canal of tooth 22 (maxillary left lateral incisor) using a radiographically guided bypass technique. A 36-year-old male patient presented for continuation of root canal treatment on tooth 22; however, during intracanal medicament placement following canal preparation, the lentulo file fractured. Periapical radiographic examination confirmed the presence of a fractured instrument along the root canal accompanied by a periapical radiolucent lesion. A bypass technique was performed under periapical radiographic guidance at every stage of the procedure, including working length determination, instrument position confirmation, and post-obturation evaluation. Post-treatment radiographic assessment demonstrated hermetic obturation with improvement of the periapical radiolucency at the three-month follow-up. This case report emphasizes that periapical radiography serves as the primary clinical guide in bypass procedures for fractured endodontic instruments within the root canal.